The Effect of Addition of Probiotic With Different Doses on Feed To The Growth And Survival Rate of Betok Fish (Anabas testudineus) With Recirculation System - Cindikia Kurniasih; Iskandar Putra; Rusliadi Rusliadi (Jurnal Akuakultur SEBATIN, 2021)
This research was conducted on from April – May 2020 at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. This research aims to obtain the best dose of probiotic added to feed for growth and survival of Betok fish (Anabas testudineus) with recirculation system. This research was using experimental method by completely random design (RAL) one factor with four treatments and three replications. The treatments were: P0 (without probiotic), P1 (probiotic of 1 g / kg of feed), P2 (probiotic of 3 g / kg of feed), P3 (probiotic of 5 g / kg of feed). The betok fish seeds used are 3-5 cm in size with a stocking density of 400 heads/m3. The results showed that the of probiotics with different doses in feed with the recirculation system has a significant effect on the growth of betok fish, feed digestibility, protein digestibility and feed efficiency, but had no significantly affect the survival of Betok fish. The best treatment was P3 (probiotic of 5 g / kg of feed) with feed digestibility of 74.5%, protein digestibility of 86.6%, feed efficiency of 73.23%, absolute weight of 5.58 g, absolute length of 3.41 cm, specific growth rate 5.63%, and survival 100%